2005
DOI: 10.1158/1078-0432.ccr-04-1887
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CXCR4 Predicts Poor Prognosis in Patients with Malignant Melanoma

Abstract: Purpose: CXCR4 receptor and its unique ligand, the CXCL12 chemokine, have been recently implicated in cancer metastasis. Evidence about the role of CXCR4/CXCL12 axis has been reported in several cancers including melanoma. Our goal was to investigate if CXCR4 expression has a prognostic value in malignant melanoma.Experimental Design: Immunohistochemical expression of CXCR4 was evaluated on 71 specimens of primary cutaneous melanoma with a Breslow tumor thickness of >1 mm after radical resection. Associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
187
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 264 publications
(203 citation statements)
references
References 32 publications
8
187
3
Order By: Relevance
“…Previous results showed that the expression of CXCR4 correlated with a worse prognosis in terms of disease-free survival and overall survival (28). Here, the analysis of the data through a KaplanMeier curve showed no statistically significant differences in terms of overall survival between patients with CXCR4À and CXCR4+ metastases (data not shown).…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Previous results showed that the expression of CXCR4 correlated with a worse prognosis in terms of disease-free survival and overall survival (28). Here, the analysis of the data through a KaplanMeier curve showed no statistically significant differences in terms of overall survival between patients with CXCR4À and CXCR4+ metastases (data not shown).…”
Section: Discussioncontrasting
confidence: 43%
“…Recently, CXCR4 was identified as an independent predictor of poor prognosis in primary melanoma (28). To evaluate the role of CXCR4 in human melanoma metastases, CXCR4 expression was analyzed in a panel of 63 melanoma metastases from melanoma patients who had undergone curative intent surgery (29 s.c., 22 lymph node, and 12 visceral metastases).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In oesophageal cancer and melanoma, CXCR4 expression is associated with poor clinical outcome [147,148]. In breast cancer, CXCR4 expression predicted lymph node metastasis [138].…”
Section: Chemokines and Their Receptors In Tumor Growth And Metastasismentioning
confidence: 99%
“…In particular, cases were considered positive when >10% of the tumor cells showed cytoplasmic and/or membrane expression. These staining and scoring methods have been widely used to evaluate the results of immunohistochemical staining for CXCR4 and CXCL12 (18,19).…”
Section: -Aza-2'-deoxycytidine (5-aza-cdr) Treatmentmentioning
confidence: 99%